Housing Based on Communal Connectivity to Enhance Resilience in Response to Rob Flood - Anisya Maharani; Wahyu Setyawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2021)
Rob flood is one of flood types caused by the increasing sea level rise submerging in area with lower level than the sea surface. With the hazard occurring regularly, this will be able to threaten the community’s vulnerability in responding to rob flood which includes social, economic, and physical impacts. With the existing housing precedents that lacks in providing a multifaceted aspect between users and its built environment, this paper aims to offer design concept based on communal connectivity to increase the resilience of community in responding rob flood. Communal connectivity focuses on the concept where communities are able to adapt and mitigate either pre-disaster, during disaster, and post-disaster. The study takes place in Semarang at Jl. Ngilir Timur that regularly has rob flood each year with 2050 as the time context. The typology offered in this design is a co-housing settlement with community resilience approach, where this approach focuses on ways to increase the communities‘adaptive capacity. Using force base framework, the main concept offered is a settlement with communal connectivity concept which focuses on several aspects in formal, spatial, material, construction, landscape, and utility. The main concept of this design mainly discusses on social connectivity and supported co-housing in formal and technical explorations which will be able to enhance community resilience in social, economy, and environment aspects.